Devil's bargain : Steve Bannon, Donald Trump, and the storming of the presidency - Green, Joshua, 1972- (2017)
The elevation of Bannon to head Trump's flagging presidential campaign on August 17, 2016, seemed to signal the meltdown of the Republican Party. Bannon was a bomb-throwing pugilist despised by Democrats and Republicans alike. Green shows that, to understand Trump's extraordinary rise and Clinton's fall, you have to weave Trump's story together with Bannon's, or else it doesn't make sense.
"It will take a miracle" -- "Where's my Steve?" -- Bildungsroman -- "A dangerous way to look at the world" -- Nobody builds walls like Trump -- The alt-Kochs -- A rolling tumbleweed of wounded male id and aggression -- "The traffic is absolutely filthy!" -- "Honest populism" -- Burn everything down -- "The FBI has learned of the existence..." -- Afterword: Kali Yugo.
Includes bibliographical references (pages [249]-263) and index.
Keywords: Bannon, Stephen K. -- Influence; Bannon, Stephen K. -- Political activity; Trump, Donald, -- 1946- -- Friends and associates; Presidents -- United States -- Election -- 2016.; Campaign management -- United States; United States -- Politics and government -- 2009-2017.